The Effect of Islamic Values–Based Assertive Training On Assertiveness Among Boarding School Students - Rasmawati, Rasmawati; Hadrayani, Eka; Azmi, Nurfadilah; Azwar, Azwar (Universitas Islam Negeri Alauddin Makassar, 2025)
Assertiveness plays a critical role in adolescents’ social adjustment, especially in boarding schools where hierarchical interactions and peer influences are strongly embedded. Limited assertiveness skills increase students’ vulnerability to psychological pressure, difficulty refusing negative peer demands, and challenges in expressing their needs appropriately. This study examined the effectiveness of Islamic values–based Assertive Training in improving assertiveness among boarding school students. A quasi-experimental pre–post test with control group design was conducted involving 93 dormitory students (46 intervention, 47 control) from a senior high school in Gowa Regency. Assertiveness was measured using the 38-item Assertive Behavior Scale (Cronbach’s α = 0.896). The intervention was delivered through five structured sessions integrating behavioral assertive training components with Islamic moral principles such as ṣidq (truthfulness), amanah (responsibility), rahmah (compassion), and adab al-kalām (proper speech). Data analysis using paired t-test showed a significant increase in assertiveness scores in the intervention group (t(45) = –14.694, p = 0.001; Cohen’s d = 2.17), indicating a very large effect size. Conversely, the control group showed no meaningful improvement (t(46) = –0.904, p = 0.371). Post-test comparison using independent t-test also revealed significantly higher assertiveness scores in the intervention group compared to the control group (p = 0.001). These findings demonstrate that Islamic values–based Assertive Training effectively enhances students’ interpersonal communication abilities and internal motivation for appropriate self-expression. The intervention model is recommended as a promotive preventive strategy to strengthen adolescents’ social competence within Islamic boarding school contexts.